Staging of Primary Abdominal Lymphomas: Comparison of Whole-Body MRI with Diffusion-Weighted Imaging and 18F-FDG-PET/CT - Alessandro Stecco; Francesco Buemi; Martina Quagliozzi; Mariangela Lombardi; Alberto Santagostino; Gian Mauro Sacchetti; Alessandro Carriero (Gastroenterology Research and Practice)
Background. The purpose of this study was to compare the accuracy of whole-body MRI with diffusion-weighted sequences (WB-DW-MRI) with that of 18F-FDG-PET/CT in the staging of patients with primary gastrointestinal lymphoma. Methods. This retrospective study involved 17 untreated patients with primary abdominal gastrointestinal lymphoma. All patients underwent 18F-FDG-PET/CT and WB-DW-MRI. Histopathology findings or at least 6 months of clinical and radiological follow-up was the gold standard. The Musshoff-modified Ann Arbor system was used for staging, and diagnostic accuracy was evaluated on a per-node basis. Results. WB-DW-MRI exhibited 100% sensitivity, 96.3% specificity, and 96.1% and 100% positive and negative predictive values (PPV and NPV), respectively. The sensitivity, specificity, and PPV and NPV of PET/CT were 95.9%, 100%, and 100% and 96.4%, respectively. There were no statistically significant differences between the two techniques p=0.05. The weighted kappa agreement statistics with a 95% confidence interval were 0.97 (0.95–0.99) between the two MRI readers and 0.87 (0.82–0.92) between the two methods. Conclusions. WB-DW-MRI appears to have a comparable diagnostic value to 18F-FDG-PET/CT in staging patients with gastrointestinal lymphoma.